PEMBUATAN MULTIMEDIA SEBAGAI UPAYA PENINGKATAN LAYANAN BANTUAN BELAJAR MAHASISWA DALAM MENGHADAPI TUGAS AKHIR PROGRAM - Istianda, Meita; Darmanto, Darmanto (LPPM Universitas Terbuka, 2009)
A final project or Tugas Akhir Program (TAP) ADPU4500 is one of the difficulties courses to be completed by students at Universitas Terbuka. It requires learning assistance that can meet the need of all UTs students. One of the learning services that is suitably developed is Compact Disk multimedia, because of its flexibilities and practicality. This research is addressed to produce Compact Disk multimedia that is easily acquired by the student and meet the students requirements. There are several steps in developing a Compact Disk multimedia, those are needs assessment, media technological option, developmental strategy and instructional design process, prototype production process, and test-driving. Needs assessment is needed to get real students requirement view. Script Writer should be intensified in production process to get production result that suits script and avoids repeated production process requiring time and expenses. Students perception of the Compact Disk multimedia TAP ADPU4500 appearance is that it is interesting and attractive. The contents can be easily studied, help students accomplish test exercises, and increase students comprehension to TAP ADPU4500. However, the Compact Disk needs to be evaluated to improve the content.